STIMULUS EKONOMI MASYARAKAT DI DESA TELUKAN KECAMATAN GROGOL KABUPATEN SUKOHARJO - Istiatin; LegowoDwi R; Sri Hartono; Ida Aryati; Ratna Damayanti; Endang Masitoh; Eni Kustiyah; Fitri Marwati (Bajang Institute, 2022)
Community service with the title community economic stimulus in Telukan Village, Grogol District, Sukoharjo Regency has been carried out on Sunday, March 27, 2022. This community service activity was held in collaboration between lecturers of the Faculty of Economics, Islamic University of Batik Surakarta with lecturers of the Pratama Mulia Polytechnic of Surakarta and Mrs. PKK Telukan Village. The purpose of this community service is to empower the community's economy by providing basic food stimulus to a group of people who are entitled to it due to the COVID-19 pandemic and other factors. The data on the recipients of the stimulus has been prepared by the PKK women in Telukan Village. The results of community service in the form of providing a package of basic food stimulus are very beneficial for the beneficiary community. The support from the PKK of Telukan Village and the Telukan village government, which was driven by the Head of Telukan Village, was very helpful in carrying out the activities. It is hoped that the provision of a package of basic food stimulus at this time feels very important and is highly expected by the people affected by the pandemic and the economy. Where all basic food prices have started to rise before the month of Ramadan in 2022. The provision of stimulus is a pattern of community empowerment entering the charity stage, where the giving is temporary that does not create dependence by the beneficiary community.